2017
DOI: 10.9790/3013-0704011014
|View full text |Cite
|
Sign up to set email alerts
|

Drain Site Abdominal Hernia: Known but Rare Complication of Abdominal Drains, a Case Report and a Review of Drain Site Complications

Abstract: Abstract:-Drains are being used in abdominal surgery since Hippocrates time therapeutically and prohpylactically aiming to reduce morbidity and early recovery of patients. But these drains are not without complications. The complications range from simple drain site infection to drain site hernia of bowel leading to strangulation and necrosis. We report a case of drain site hernia (DSH) in a 47 year-old women who presented with obstructed large incisional hernia through a previous laparotomy scar. During surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Common complications of placing drains include drain site sepsis, bleeding, migration, kinking and knotting of drains, intestinal obstruction, fistulae or erosion into viscera with peritonitis and herniation. [ 1 2 ] Several case reports are there in the literature, documenting evisceration of multiple organs from larger drain site such as small bowel, omentum, appendix, fallopian tube, ovary and gallbladder,[ 3 4 ] with the most common being small bowel. [ 2 ] Almost all these cases were open surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Common complications of placing drains include drain site sepsis, bleeding, migration, kinking and knotting of drains, intestinal obstruction, fistulae or erosion into viscera with peritonitis and herniation. [ 1 2 ] Several case reports are there in the literature, documenting evisceration of multiple organs from larger drain site such as small bowel, omentum, appendix, fallopian tube, ovary and gallbladder,[ 3 4 ] with the most common being small bowel. [ 2 ] Almost all these cases were open surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Evisceration has been documented with smaller drains (6 mm), suggesting that size is not the only factor despite the fact that most cases were reported in patients with a drain size of 10 mm or more. [ 1 3 6 ] Rather than the size, the nature of tract plays an important role. Usage of port site for drain placement increases the risk of evisceration as they have a straight tract which does not approximate well on deflating pneumoperitoneum unlike a zigzag tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] Out of these most common was small bowel loops and appendix. [9][10][11] Omentum was found as a content in very few cases as reported by Bakka et al and Samarawickrama et al 12,13 There are cases in literature found to have drain site hernia with small bowel and omentum as content but none of the case is found to have bilateral drain site hernia.…”
Section: Discussionmentioning
confidence: 99%
“…A particular drain could serve any combination of these purposes. Intra-peritoneal drain placement is however associated with some risks ranging from minor unnoticeable, through life-altering such as infertility, to life-threatening as in the case of visceral evisceration or perforation (3,4,5,6). The benefit of routine drain placement for different varieties of abdominal surgeries has remained a debate in contemporary times (4,5,7,8).…”
Section: Introductionmentioning
confidence: 99%